A participatory Bayesian Belief Network approach to explore ambiguity among stakeholders about socio-ecological systems. (October 2017) - Salliou, Nicolas; Barnaud, Cécile; Vialatte, Aude; Monteil, Claude
Abstract: Participatory modelling must often deal with the challenge of ambiguity when diverse stakeholders do not share a common understanding of the problem and measures for its solution. In this paper, we propose a framework and a methodology to elicit ambiguities among different stakeholders by using a participatory Bayesian Belief Network (BBN) modelling approach. Our approach consists of four steps undertaken with stakeholders: (1) co-construction of a consensual conceptual model of their socio-ecological system, (2) translation of the model into a consensual Bayesian Net structure, (3) individual parametrization of conditional probabilities, and (4) elicitation of ambiguity through the use of scenarios. We tested this methodology on the ambiguity surrounding the effect of an ecological process on a potential innovation in biological control, and it proved useful in eliciting ambiguity. Further research could explore more conflictual or controversial ambiguities to test this methodology in other settings. Highlights: A participatory Bayesian Belief network method is proposed to sort out ambiguities among different stakeholders. The method is based on participation of stakeholders all along, from framing the research question to scenario exploration. The case study explored the ambiguities between local agricultural stakeholders and a landscape ecology scientist.